ROMAN AMPHORAE FROM THE EAST ALONG THE RIPA PANNONICA - Hárshegyi, Piroska (Rei Cretariae Romanae Fautorum Acta, 2024)
Reviewing some earlier and more recent finds from Pannonian archaeological sites we can distinguish amphora types of eastern origin in increasing numbers. Since the last comprehensive study by T. Bezeczky, most of the data concerning amphorae from the Roman East are available from the Danube frontier area.